Effects of Training and Workload of Teachers’ on Achievement of Students’ in Mathematics in Senior Schools in Jos Metropolis, Plateau State, Nigeria - Attah, Bala G.; Adebayo, Olubukola J. (NIU Journal of Humanities, 2018)
The attainment of excellent achievement of students in Mathematics hinged on the training and workload of teachers in schools. Excellent achievement of students does not occur by chance unless some factors are looked into. Much task in terms of teaching units and assignment to Mathematics teachers, can make or mar the achievement of students in the schools. The interplay was a rallying point of this study which tried to ascertain the effect of training and workload of teachers’ on achievement of teachers’ in Jos metropolis Plateau State, Nigeria. Theoretically, the present study was on Skinner’s theory of Operant Conditioning. As a descriptive study which made use of descriptive research survey type of research design, it consisted of two research questions and two null hypotheses tested at 5% level of significance with 10 teachers and 450 students. The Mock results of teachers’ from Jos metropolis of Plateau State were used. Two sets of questionnaire were generated as basic instruments for data collection which comprised of effect of teachers’ training on students’ achievement and effect of teachers’ workload on students’ achievement in mathematics. Findings revealed that there was significant relationship between teachers’ training and students’ achievement (r=0.824, P-value=0.009). It was also revealed that there was significant relationship between teachers’ workload and students’ achievement (r=0.777; P-value= 0.008). Finally, the senior schools Mathematics teachers’ workload and training have effects on students’ achievement and therefore government should employ well trained teachers with adequate workload in teaching mathematics. The Mathematics teachers should be allowed to attend seminars and workshops as this will contribute to teachers’ understanding of the changes in education system in Nigeria and the globe. Keywords: Teachers’ Training, Workload and Students’ Achievement